Design and Optimization of a Large-Stroke Compliant Constant-Torque Mechanism - Phan, Thanh Vu; Pham, Huy-Tuan (Journal of Technical Education Science, 2022)
Compliant constant-torque mechanism (CTM) can produce an output torque that does not change within a prescribed input rotation range. This stability is maintained regardless of complicated sensorized control systems. Owing to the monolithic nature of the compliant mechanism, the device is more compact, lightweight, and portable, which is favorable to human joint rehabilitative devices or mobility-assisting devices. However, before approaching the stable range, the mechanism has to undergo a pre-loading range which usually accounts for one-third of the entire operational journey. In addition, the deformation of flexible segments is restricted due to the yield strength of the materials. This limited working range hampers other potential applications of compliant CTMs. This paper presents a novel design of a compliant 2-stage CTM with long-stroke by using serially connected curved beams that deform sequentially. The design process is implemented via a shape optimization scheme using genetic algorithm. Finite element analysis is used to characterize the constant-torque behavior of the CTM under static loading. A general design formulation is also proposed to synthesize this special kind of compliant mechanism. The results show that this CTM gets the stable torque range from 300 to 1100 over two stages with the deviation less than 4.3%.